Theoretical Studies to Estimate the Skin Sensitization Potential of Chemicals of the Schiff Base Domain. - Duangkamol Gleeson; Matthew Gleeson (My University, 2019)
Skin sensitization occurs when an exogenous chemical substance forms a covalent adduct with a dermal protein electrophile or nucleophile. This instigates an immune response which leads to inflammation. The local lymph node assay (LLNA) is an in-vivo model used in the assessment of relative skin sensitizing potency of chemicals. The method is time consuming and expensive, as well as poses ethical questions given that a number of mice must be sacrificed for each compound assessed. In this work we investigate the use of an inexpensive, rapid and ethical method to predict the skin sensitization potential of Schiff base chemicals. We employ quantum chemical methods to rationalize the sensitization potential of 22 compounds with a diverse range of activities. To this end we have evaluated the mechanistic profile associated with this type of reaction using gas-phase models. We subsequently use the predicted rate determining barriers and key physico-chemical parameters (such as logP) to establish SAR guidelines to predict the skin sensitization potential for new chemicals. We find that the predicted rate determining barriers for aldehydes, ketone and 1,2 and 1,3 diones generally decrease in the given order, which concurs with the overall trends in sensitization. We find that lipophilicity also plays a role, with those chemicals displaying both low barriers to reaction, and lower lipophilicity (i.e. diones), being more likely to display undesirable skin sensitization effects. These findings are in line with experimental based observations in the literature and point to the value 3D quantum chemical simulations can play in the combination of approaches used to estimate skin sensitization potential of chemicals.
Keywords: Lipophilicity; Chemistry and Chemical Engineering